(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Informal Auto Rickshaw and Commercial Taxi Drivers in Nagaon urban areas are vulnerable to variety of health problems and other welfare insecurities as they are none but the urban poor. Poor working conditions, non-affordability to health care are some of the reasons that results in diseases, injuries both fatal and non-fatal to the workers. With the aim of exploring such health and other issues of the drivers in the Nagaon Town of Assam a descriptive study was carried out among 120 Drivers from two groups (80 from Auto Rickshaw and 40 from Commercial Taxi) using convenience sampling technique. Study found multiple health problems among the Drivers in the area. Self-employed drivers from both the groups were found affected in large numbers. Lowest 5 to highest 70 Auto drivers and lowest 7.5 to highest 60 of Taxi drivers were found multiple disease affected. Non-fatal injury affected drivers were also found among highest 37.5 drivers. Health care access was found in poor state and non-availability of social security to the drivers raised a great concern. Govt intervention, community participation, awareness and surveillance are some of the suggestions extended by the study.